Los Juegos Tradicionales en el desarrollo de la Expresión Corporal en los niños del subnivel Inicial del proyecto SAFPI de la Parroquia Poaló, en el año lectivo 2022-2023. - Martínez Uribe, Blanca Sofía (2023)
The research work that has been presented was focused on the analysis of the benefits that the use of traditional games can bring, taking into consideration the specific problem of the lack of development of corporal expression in children of the Initial Education sublevel of the project. SAFPI of the Poaló Parish. The objective of the research was to encourage the use of traditional games in the development of corporal expression in children of the initial sub level of the SAFPI project of the Poaló Parish in the 2022-2023 school year. The applied methodology had a qualitative approach, with the application of the inductive method, to reach the level of descriptive research, the type of applied research was bibliographic and field, through the interview techniques directed to the authority, educator and parents and observation applied to children of the SAFPI Project.